Utilization Of the Sarekat Islam Building in Semarang As A Living History Learning Model for History Subjects During The Indonesian Movement - Khotimah, Siti Khusnul (History Education, University of Jember, 2023)
This article contains the history of the establishment of the Sarekat Islam building, including the background to the establishment of the building, its functions, and its development over time. Later from this research it can be linked to history learning, both in terms of its benefits and its application in education. The struggle of the heroes needs to be told to students clearly by utilizing historical relics such as buildings or objects related to historical events. The lack of interest of students in exploring history and the existence of historic buildings that have not been utilized optimally is the reason for this research being conducted. The introduction of the Sarekat Islam building will later use the living history learning model. This model utilizes the surrounding environment to channel learning objectives. It is expected that students can understand the meaning of learning history. The method used in this research is the literature study method. This means that researchers utilize previous sources related to the problem to be solved to complete the research. The purpose of this research is to encourage students to think chronologically, be active, and have a high spirit of nationalism. On the other hand, with this paper it is hoped that history educators can make historical references. Keywords: Sarekat Islam Building in Semarang, living history, movement history